2015
DOI: 10.1364/boe.7.000013
|View full text |Cite
|
Sign up to set email alerts
|

Retinal safety of near infrared radiation in photovoltaic restoration of sight

Abstract: Photovoltaic restoration of sight requires intense near-infrared light to effectively stimulate retinal neurons. We assess the retinal safety of such radiation with and without the retinal implant. Retinal damage threshold was determined in pigmented rabbits exposed to 880nm laser radiation. The 50% probability (ED50) of retinal damage during 100s exposures with 1.2mm diameter beam occurred at 175mW, corresponding to a modeled temperature rise of 12.5°C. With the implant, the same temperature was reached at 78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…According to the thermal safety standard for active implantable medical devices (ISO 14708-1 / EN 45502-1), the maximum temperature on the surface of the implant should not exceed 2 °C above the normal surrounding body temperature of 37 °C 31 . We measured in air the increase in temperature on the POLYRETINA surface (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to the thermal safety standard for active implantable medical devices (ISO 14708-1 / EN 45502-1), the maximum temperature on the surface of the implant should not exceed 2 °C above the normal surrounding body temperature of 37 °C 31 . We measured in air the increase in temperature on the POLYRETINA surface (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The threshold in the RCS rats was found to be ~ 1 mW/mm 2 , exceeding the natural retinal irradiance by a factor of 1,000 (Lorach et al, 2015b). The investigators argue that the pulsed delivery of NIR at this intensity level results in an average irradiance far below the maximum permissible dose of NIR to retina for chronic exposure (Lorach et al, 2016). Since it's not clear from the group's publications whether long term changes occurred at the implant-retina interface, physically and functionally, their arguments in terms of ocular safety awaits further verification.…”
Section: Photovoltaic Retinal Prosthesismentioning
confidence: 95%
“…Detailed studies of retinal heating with and without silicon implants under various illumination conditions have shown that under typical use conditions, the temperature increase associated with activation of a subretinal photovoltaic implant is not expected to exceed 0.5°C, well within the safety limits for chronic use [70]. …”
Section: Approaches To Retinal Prostheticsmentioning
confidence: 99%